Baseline Neurocognitive Impairment (NCI) Is Associated With Incident Frailty but Baseline Frailty Does Not Predict Incident NCI in Older Persons With Human Immunodeficiency Virus (HIV). (13th February 2021) - Masters, Mary Clare; Perez, Jeremiah; Wu, Kunling; Ellis, Ronald J; Goodkin, Karl; Koletar, Susan L; Andrade, Adriana; Yang, Jingyan; Brown, Todd T; Palella, Frank J; Sacktor, Ned; Tassiopoulos, Katherine; et al.
Abstract: Background: Neurocognitive impairment (NCI) and frailty are more prevalent among persons with human immunodeficiency virus (HIV, PWH) compared to those without HIV. Frailty and NCI often overlap with one another. Whether frailty precedes declines in neurocognitive function among PWH or vice versa has not been well established. Methods: AIDS Clinical Trials Group (ACTG) A5322 is an observational cohort study of older PWH. Participants undergo annual assessments for NCI and frailty. ACTG A5322 participants who developed NCI as indexed by tests of impaired executive functioning and processing speed during the first 3 years were compared to persons who maintained normal cognitive function; those who demonstrated resolution of NCI were compared to those who had persistent NCI. Participants were similarly compared by frailty trajectory. We fit multinomial logistic regression models to assess associations between baseline covariates (including NCI) and frailty, and associations between baseline covariates (including frailty) and NCI. Results: In total, 929 participants were included with a median age of 51 years (interquartile range [IQR] 46–56). At study entry, 16% had NCI, and 6% were frail. Over 3 years, 6% of participants developed NCI; 5% developed frailty. NCI was associated with development of frailty (odds ratio [OR] = 2.06; 95% confidence interval [CI] = .94, 4.48; P = .07). Further adjustment for confounding strengthened this association (OR = 2.79; 95% CI = 1.21, 6.43; P = .02). Baseline frailty however was not associated with NCI development. Conclusions: NCI was associated with increased risk of frailty, but frailty was not associated with development of NCI. These findings suggest that the presence of NCI in PWH should prompt monitoring for the development of frailty and interventions to prevent frailty in this population. Abstract : In a large cohort of persons with human immunodeficiency virus (HIV, PWH), neurocognitive impairment (NCI) was associated with development of frailty, but frailty was not associated with development of NCI. These findings provide insight into the relationship between NCI and frailty in PWH.